عوامل الشخصية المنبئة بالاحتراق النفسي لدى معلمي التربية الخاصة - لحول, فايزة (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة إلى معرفة مستوى الاحتراق النفسي لدى معلمي التربية الخاصة، والكشف عن مدى إسهام عوامل الشخصية الخمسة الكبرى المتمثلة في: العصابية، الانبساطية، الصفاوة، الطيبة ويقظة الضمير في التنبؤ بالاحتراق النفسي لمعلم التربية الخاصة، من خلال دراسة ميدانية على عينة قوامها 50 معلما من العاملين بالمراكز الطبية البيداغوجية للمعاقين ذهنيا، مدرسة المعاقين سمعيا، ومدرسة الأطفال المعاقين بصريا بولايتي عين الدفلى والشلف. تم اتباع المنهج الوصفي، وتطبيق مقياس ماسلاش للاحتراق النفسي (1984) ومقياس عوامل الشخصية الخمسة الكبرى لكوستا وماكري(1998) توصلت النتائج إلى: وجود مستوى مرتفع من الاحتراق النفسي لدى معلمي التربية الخاصة، مع إمكانية التنبؤ بالاحتراق النفسي لديهم من خلال عامل الطيبة، حيث فسر العامل ما نسبته حوالي 18,2℅ من تباين درجات المعلمين في الاحتراق النفسي. Abstract: The study aimed to detect the level of burnout among special education teachers, and to reavel the contribution of the big five personality factors (Neuroticism, Extraversion, Agreeableness, Opness to experience and Conscientiousness) to the prediction of burnout among special education teacher, the study sample incuded 50 teachers, Of the workers in the pedagogical medical centers for the mentally handicapped, the Deaf Young School and the Visually Impaired School in Ain Defla and Chlef. The descriptive approach was followed, we used the Maslach Burnout test (1984), and the Five Big Personality Factors test for Costa & Mc Crae (1998). Results of the study indicated that special education teachers suffer from high level of burnout, Results also indicated predictability of burnout through one factors : Agreeableness, where the factor explained about 18.2℅ of burnout.
مقال
Keywords: احتراق نفسي ; معلم ; تربية خاصة ; تنبؤ ; شخصية; Burnout; Teacher; Special education; Prediction; Personality